Identifying the patterns and drivers of Puumala hantavirus enzootic dynamics using reservoir sampling. Issue 1 (22nd April 2019) - Laenen, Lies; Vergote, Valentijn; Vanmechelen, Bert; Tersago, Katrien; Baele, Guy; Lemey, Philippe; Leirs, Herwig; Dellicour, Simon; Vrancken, Bram; Maes, Piet
Abstract: Hantaviruses are zoonotic hemorrhagic fever viruses for which prevention of human spillover remains the first priority in disease management. Tailored intervention measures require an understanding of the drivers of enzootic dynamics, commonly inferred from distorted human incidence data. Here, we use longitudinal sampling of approximately three decades of Puumala orthohantavirus (PUUV) evolution in isolated reservoir populations to estimate PUUV evolutionary rates, and apply these to study the impact of environmental factors on viral spread. We find that PUUV accumulates genetic changes at a rate of ∼10 −4 substitutions per site per year and that land cover type defines the dispersal dynamics of PUUV, with forests facilitating and croplands impeding virus spread. By providing reliable short-term PUUV evolutionary rate estimates, this work facilitates the evaluation of spatial risk heterogeneity starting from timed phylogeographic reconstructions based on virus sampling in its animal reservoir, thereby side-stepping the need for difficult-to-collect human disease incidence data.